Strategi Merespon Pujian pada Pembelajar Bahasa Jepang: Kajian Komparatif dengan Penutur Asli - Rosi Rosiah (JLA (Jurnal Lingua Applicata), 2018)
This study compares the use of responding praise strategies by 20 subjects of Japanese language learners and 20 native speakers. Using DTC (Discourse Complement Test) as an instrument which consists of 18 situations, the data of 360 sentences were then analyzed using a semantic formula from the concept of Korsatianwon Sayan (2003) that divides the response of praise into 15 strategies, namely: gratitude, approval expression, happy expression, praise upgrade, disagreement, suspect intent, comment acceptance, reassignment, empty, return, question, change topic, scale down, laugh and shame or shock. In conclusion, many Japanese language learners respond to praise with the strategy of rejecting praise. This is in accordance with the concept of ‘refusing praises’ in the East, which means humbling ourselves. Meanwhile, the native speakers of Japanese respond to praise with ‘being grateful’ strategy. This is in accordance with the conception of ‘thank you’ in the West to respond to praises, which aims to maintain the positive face of the other person.